1974
DOI: 10.1083/jcb.62.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Redistribution of Surface-Bound Concanavalin a on Human Polymorphonuclear Leukocytes

Abstract: Human neutrophil polymorphonuclear leukocytes (PMN) were studied to determine the influence of cellular locomotion upon the redistribution and capping of concanavalin A (Con A) . Con A was detected by fluorescence (using Con A conjugated to fluorescein isothiocyanate [Con A-FITC]), or on shadow-cast replicas (using Busycon canaliculatum hemocyanin as a marker for Con A) . After labeling with Con A 100 µg/ml at 4°C and warming to 37°C, locomotion occurred, and the Con A quickly aggregated into a cap at the trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

1976
1976
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…Ryan et al (1974) did observe a gradient of fluorescence labeling on polymorphonuclear leucocytes. Braun et al (1978) reported that some membrane proteins were concentrated in one end of pre-fixed polarized lymphocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Ryan et al (1974) did observe a gradient of fluorescence labeling on polymorphonuclear leucocytes. Braun et al (1978) reported that some membrane proteins were concentrated in one end of pre-fixed polarized lymphocytes.…”
Section: Discussionmentioning
confidence: 97%
“…This network could then either transfer the message to other parts of the cell or itself direct the rearrangement, de Petris (14) has suggested that such a network could be provided by microfilaments because of the effects of cytochalasin B on label-induced rearrangement. He and others (44,56) have found a cooperative inhibitory effect of cytochalasin B and colchicine on capping, indicating that a microtubule system may be involved as well. Networks of microfilamerits (49) and microtubules (40) are present below the cell surface, but there is no absolutely conclusive evidence for the direct involvement of such networks in the arrangement of surface molecules.…”
Section: Discussionmentioning
confidence: 99%
“…(b) The serine proteases might be associated with the movement of the macromolecules in the surface membrane; as it has been suggested that the triggering of the metabolic activation of phagocytic cells is provided by a surface redistribution of the ligand-receptor complexes, which may perturb the surface membrane to activate the NAD(P)H oxidase (30). If this is the case, it may be possible that impaired movement of the macromolecules in the surface membrane may also contribute to the inhibition of chemiiotaxis and phagocytosis in addition to°2 production by serine protease inhibitors, inasmuch as chemotaxis and phagocytosis also accompany the movement of the macromolecules in the surface membrane (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%